KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL (EQ) DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI I KARTA KECAMATAN KOTA AGUNG TIMUR KABUPATEN TANGGAMUS TAHUN AKADEMIK 2022/2023 - Purwani, Yuli; Syahril, Sulthan; Yanti, Dewi (UNISAN JURNAL, 2023)
This study aims to examine the implementation of emotional intelligence-based school leadership in SD Negeri 1 Karta, in which researchers use research indicators from the Fleishman leadership dimension: initiative and concern. From the initiative dimension there are 1) leader ethos, 2) initiative intuition, and 3) allocation of responsibility, while from the leader's concern dimension are 1) attention to the work and process to get it, and 2) attention to employee welfare. This qualitative research uses a case study design and is followed by data collection through interviews, participatory observation, and documentation studies. The results of this study are 1) school leaders have carried out leadership initiatives, proven by effective and efficient work in regulating the rights and obligations of school members, and 2) thanks to very good attention, leaders can maintain good school conditions. Leaders also continue to improve employee welfare by increasing their income and have succeeded in increasing knowledge and skills for both teachers and employees..